A kind of anti-swelling, underwater adhesion conductive composite hydrogel and its preparation method and application

By using a composite system of lignocellulose nanofiber fibers, silver salts and dimethyl sulfoxide, a high-density cross-linking network is built, which solves the problem of conductive hydrogel swelling in humid environments, and achieves multifunctional properties of swelling, mechanical strength, frost resistance and underwater adhesion, and is suitable for underwater communication and other fields.

CN119144018BActive Publication Date: 2025-03-07ZHEJIANG FORESTRY UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411604057.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing conductive hydrogels are prone to swelling in humid environments, resulting in attenuation of mechanical and electrical properties, limiting their application in underwater communication and other fields.

Method used

A composite system of lignocellulose nanofiber filaments, silver salts and dimethyl sulfoxide is adopted to form a high-density crosslinking network by constructing a reversible redox reaction, multiple hydrogen bonding and nano-enhancement effect to achieve a conductive hydrogel that is resistant to swelling, mechanical strength, frost and underwater adhesion.

Benefits of technology

It realizes the rapid preparation of conductive hydrogels (200s~1200s), with high conductivity, excellent frost resistance, excellent underwater adhesion and mechanical properties, and is suitable for flexible sensing applications under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144018B_ABST
    Figure CN119144018B_ABST
Patent Text Reader

Abstract

The present invention discloses a swelling-resistant, underwater-adhesive conductive composite hydrogel and its preparation method and application, belonging to the field of polymer materials. The method comprises adding monomers, gelatin, a cross-linking agent, a silver salt and an initiator to a water dispersion of lignocellulose nanofibrils, mixing the mixture evenly with dimethyl sulfoxide, and standing the mixture for a period of time at room temperature to obtain the conductive hydrogel. The conductive hydrogel prepared by the present invention has excellent comprehensive properties, including mechanical, electrical, swelling-resistant, underwater adhesion and strain sensing properties, and is suitable for the field of underwater communication sensors. Moreover, the preparation method adopted by the present invention is green, environmentally friendly, simple and easy to operate, low in cost, and easy to promote and apply in the market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and relates to a method for preparing a swelling-resistant, underwater-adhesive conductive composite hydrogel and an application of the composite hydrogel in underwater communication sensing. Background Art

[0002] Conductive hydrogel is a multifunctional integrated soft material with the characteristics of mechanical flexibility, conductivity and biocompatibility. Therefore, it shows great application prospects in the fields of electronic skin, flexible sensor devices and motion monitoring. However, in practical applications, this material will inevitably face a humid environment, and the hydrophilic polymer network will easily induce water molecules to penetrate into the matrix, resulting in swelling. This will seriously affect the structural stability of the gel network, causing a significant attenuation of the mechanical / electrical properties. In a high water content atmosphere or water environment, the application field of conductive hydrogels, especially underwater communications, is greatly limited. Therefore, how to give conductive hydrogels anti-swelling properties while maintaining their excellent mechanical and electrical properties is an urgent and meaningful research topic for this material.

[0003] In response to the above problems, researchers have improved the water repellency of the gel by constructing a high-density cross-linked network, introducing hydrophobic components, and constructing a surface hydrophobic protective layer, thereby improving its anti-swelling performance. The patent with publication number CN118184872A discloses a method for preparing a conductive polymer hydrogel. By introducing the hydrophobic monomer 2-hydroxyethyl methacrylate and combining solvent replacement to form an ordered network structure, the anti-swelling performance of the hydrogel is improved. However, the solvent replacement method used is difficult to effectively control the conversion of organic gel to hydrogel, and the operation is difficult. In addition, the mechanical ductility of the gel is poor, and its elongation at break is only 519%. Gao et al. prepared an anti-swelling composite conductive hydrogel using γ-PGA and PVA as the main components. Multiple hydrogen bonds are formed between polymer chains through repeated freeze-thaw cycles, thereby increasing the cross-linking density of the hydrogel and giving it excellent underwater anti-swelling properties. However, the system lacks an efficient conductive mechanism, and the conductivity of the hydrogel is only 0.94S⋅m -1 , which is far from the actual performance requirements. It is worth pointing out that the above anti-swelling systems still have disadvantages such as many preparation steps, long preparation cycle and high requirements for process environment, which seriously limit the development and further application of anti-swelling hydrogels. Therefore, how to achieve the construction of anti-swelling conductive hydrogels in a short time without external energy is the key to expanding its practical application. Pi et al. constructed MXene / zirconium ion (Zr 4+ ) Autocatalytic system, Zr 4+The formation of coordination bonds with the carboxyl groups on the polymer chain accelerates the formation of the polymer network, thereby realizing the rapid preparation of anti-swelling conductive hydrogels at room temperature. However, the high cost of preparing MXene in this system, the complex process and poor room temperature oxidation resistance are not conducive to practical industrial applications. In addition, the lack of adhesion, especially underwater self-adhesion, means that the gel can only be used underwater for a long time with the help of tape.

[0004] In summary, although some progress has been made in the field of anti-swelling conductive hydrogels, it is still difficult to achieve rapid construction of multifunctional integration, especially mechanical, anti-swelling and underwater adhesion. Therefore, developing an anti-swelling, mechanically tough, anti-freezing, underwater adhesion conductive composite hydrogel is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide an anti-swelling, underwater adhesive conductive composite hydrogel and a preparation method and application thereof to address the problems existing in the prior art.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] The first technical purpose of the present invention is to provide a method for preparing an anti-swelling, underwater-adhesive conductive composite hydrogel, which uses a composite system of lignocellulose nanofibrils, silver salt and dimethyl sulfoxide to achieve the preparation of an anti-swelling, mechanically tough, antifreeze, underwater-adhesive conductive hydrogel, and at least comprises the following steps:

[0008] To 0.1-0.5 parts of an aqueous dispersion containing 5-50 wt% nano-concentration wood cellulose nanofibrils, 1-5 parts of an acrylic monomer, 0.1-0.5 parts of gelatin, 0.01-0.05 parts of a cross-linking agent, 0.01-0.05 parts of a silver salt and 0.01-0.035 parts of an initiator are added, followed by uniform mixing with 1-5 parts of dimethyl sulfoxide to obtain a gel precursor, which is allowed to stand at room temperature for 200-1200 s to obtain an anti-swelling, underwater adhesive conductive composite hydrogel.

[0009] Among them, the hydroxylated lignocellulose nanofibrils, phosphorylated lignocellulose nanofibrils or sulfonated lignocellulose nanofibrils have a catechol structure on their surface; in the preparation system of the present invention, the reversible redox reaction between the phenol groups on the surface of the lignocellulose nanofibrils and the silver ions is utilized to greatly reduce the decomposition energy of the initiator, so that free radicals are generated. On this basis, the formation of hydroxyl radicals can be induced to achieve room temperature free radical polymerization of the monomer.

[0010] The ionic conductive mechanism constructed by silver ions and nanofibrils gives the hydrogel high conductivity. The nano-enhancement effect of nanofibrils combined with multiple hydrogen bonds can also effectively enhance the polymer network and improve the mechanical properties. At the same time, due to the formation of strong hydrogen bonds between polymer chains, the density of the network structure is improved, which can effectively inhibit the entry of water molecules to achieve the anti-swelling properties of the hydrogel. The introduction of dimethyl sulfoxide can form hydrogen bonds with water molecules, which can lower the freezing point of the system and achieve its structural stability in a low-temperature environment. In summary, the present invention uses a composite of lignocellulose nanofibrils, silver salts and dimethyl sulfoxide to achieve rapid preparation of the system (200s~1200s), while also achieving the product's anti-swelling, high mechanical, antifreeze, underwater adhesion and conductive properties.

[0011] Optionally, the lignocellulose nanofibrils are at least one of hydroxylated lignocellulose nanofibrils, phosphorylated lignocellulose nanofibrils, and sulfonated lignocellulose nanofibrils, and the surfaces of the lignocellulose nanofibrils have a catechol structure.

[0012] Furthermore, the preparation method of the lignocellulose nanofibrils is as follows:

[0013] At room temperature, 4-400 parts of urea, 1-20 parts of an acidifying agent, and 0.5-10 parts of bamboo powder are added to 20-1000 parts of water, followed by mechanical stirring until the solution is uniform, the resulting suspension is poured into a container and dried to constant weight in a blast oven; the resulting solid is then placed at 50-200°C for 30-120 min, dispersed with water and neutralized with an alkali solution; the resulting suspension is dialyzed to neutrality, and lignocellulose nanofibrils are obtained by mechanical grinding; the acidifying agent is diammonium hydrogen phosphate or ammonium hydrogen sulfate.

[0014] It should be noted that cellulose nanofibrils are abundant in sources and simple to prepare; as nano-reinforced fillers, their high aspect ratio and abundant active groups (hydroxyl groups) can form strong hydrogen bonds with polymer chains, effectively exerting their nano-reinforcement effect. Moreover, the surfaces of the wood cellulose nanofibrils all have catechol structures, so they can form a reversible redox system with silver ions, inducing rapid free radical polymerization of monomers at room temperature.

[0015] Preferably, the acrylic monomers include acrylic acid, methyl acrylate, ethyl acrylate, lauryl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, hydroxypropyl methacrylate or methacrylic acid. The monomers used in the present invention have high reactivity, low price and are easily available.

[0016] Preferably, the molecular weight of the gelatin is 10000 to 70000. The addition of gelatin can form multiple hydrogen bonding sites, which helps to build a dense network structure, giving the gel high mechanical properties while effectively preventing the penetration of water molecules and obtaining anti-swelling properties.

[0017] Preferably, the cross-linking agent includes N,N'-methylenebisacrylamide, N,N'-bis(acryloyl)cystamine, ethylene glycol diacrylamide or N,N'-(1,2-dihydroxyethylene)diacrylamide.

[0018] Preferably, the silver salt is at least one of silver nitrate or silver perchlorate. The addition of silver ions can form a reversible redox system with the lignocellulose nanofibrils, which can reduce the decomposition energy of the initiator and achieve rapid free radical polymerization of the monomer induced at room temperature; on the other hand, the nanofibrils can construct an ion conduction mechanism, giving the hydrogel high conductivity, laying the electrical performance foundation for subsequent sensing applications.

[0019] Preferably, the initiator comprises potassium persulfate, ammonium persulfate or sodium persulfate.

[0020] The second technical purpose of the present invention is to provide an anti-swelling, underwater adhesive conductive composite hydrogel prepared by the method as described above.

[0021] The third technical purpose of the present invention is to provide an anti-swelling, underwater adhesive conductive composite hydrogel prepared by the method as described above for use in human motion monitoring and underwater communication sensing.

[0022] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides an anti-swelling, underwater adhesive conductive composite hydrogel and its preparation method and application, which have the following excellent effects:

[0023] The multifunctional composite hydrogel prepared by the present invention has fast and controllable room temperature gelation, excellent and balanced mechanical properties, high conductivity, excellent antifreeze property, outstanding underwater adhesion and underwater strain-induced resistance change characteristics.

[0024] Based on the above excellent comprehensive properties, this composite hydrogel has great potential application value in the field of flexible sensing (underwater strain sensor) under extreme conditions and is suitable for market promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0026] Figure 1 These are digital photos and infrared thermal images of the rapid gelation process of the composite hydrogel corresponding to Example 10.

[0027] Figure 2 These are stress-strain curves of the hydrogels synthesized in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 10.

[0028] Figure 3 This is a digital photo of the macroscopic mechanics of the composite hydrogel synthesized in Example 10.

[0029] Figure 4 This is the swelling curve of the composite hydrogel synthesized in Example 10.

[0030] Figure 5 These are digital photos of the underwater adhesion of the composite hydrogel synthesized in Example 10 to different substrates.

[0031] Figure 6 These are digital photos of the composite hydrogels synthesized in Comparative Example 3 and Example 10 after standing at -20°C for 30 days.

[0032] Figure 7 This is a schematic diagram of the composite hydrogel synthesized in Example 10 being used for underwater Morse code compilation. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0035] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0036] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0037] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0038] The present invention discloses a swelling-resistant, underwater-adhesive conductive composite hydrogel and its preparation method and application, which adopts a composite system of lignocellulose nanofibrils and metal ions, and realizes the mechanical property enhancement, swelling-resistant and functional property integration of the polymer network structure by constructing a reversible redox system, multiple interactions, nano-enhancement effect and the introduction of silver salt, and finally obtains a multifunctional integrated (swelling-resistant, mechanically tough, antifreeze, underwater adhesion, strain sensing) composite hydrogel. A swelling-resistant, underwater-adhesive conductive composite hydrogel is obtained by adding monomers, gelatin, crosslinking agents, silver salts and initiators to a lignocellulose nanofibril aqueous dispersion, mixing them evenly with dimethyl sulfoxide, and standing them at room temperature for a period of time.

[0039] In addition, the reversible redox system formed between the lignocellulose nanofibrils and the silver ions reduces the decomposition energy of the initiator and realizes the rapid free radical polymerization of the induced monomer at room temperature. At the same time, the nano-enhancement effect of the nanofibrils combined with the multiple hydrogen bonding can enhance the polymer network structure and realize the mechanical toughness of the conductive hydrogel. The ion channels constructed by the silver ions and nanofibrils also give it good conductivity. The polyhydroxy structure of gelatin enables it to form strong hydrogen bonds with the polymer chains, and the density of the network structure is improved, thereby effectively inhibiting the entry of water molecules, realizing the anti-swelling characteristics of the hydrogel, and laying a performance foundation for the subsequent application in the field of underwater communication sensors.

[0040] The monomers, initiators, silver salts, crosslinking agents and wood cellulose nanofibrils used in the present invention are all existing products.

[0041] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention. Embodiment 1

[0042] 1) At room temperature, 0.7 g of bamboo powder was added into 500 mL of water, followed by mechanical stirring until the solution was uniform, and finally mechanical grinding was performed to obtain hydroxylated lignin cellulose nanofibrils.

[0043] 2) adding 20.8 g of isobornyl acrylate, 7 g of gelatin, 0.22 g of N,N'-bis(acryloyl)cystamine, and 0.8 g of silver nitrate by weight to 60 mL of an aqueous dispersion containing 15 wt% of hydroxylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0044] 3) At room temperature, 7.8 g of sodium persulfate and 1.56 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 500 s. Embodiment 2

[0045] 1) At room temperature, 4 g of urea, 1 g of diammonium hydrogen phosphate, and 0.5 g of bamboo powder were added to 400 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 70 ° C for 60 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally phosphorylated lignocellulose nanofibrils were finally obtained by mechanical grinding.

[0046] 2) adding 13.2 g of methyl acrylate, 0.78 g of gelatin, 0.08 g of N,N'-methylenebisacrylamide, and 1.08 g of silver nitrate by weight to 70 mL of an aqueous dispersion containing 5 wt% of phosphorylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0047] 3) At room temperature, 4.4 g of ammonium persulfate and 0.3 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 300 seconds. Embodiment 3

[0048] 1) At room temperature, 70 g of urea, 4 g of ammonium bisulfate, and 0.8 g of bamboo powder were added to 600 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 100 ° C for 120 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally the sulfonated lignin cellulose nanofibrils were finally obtained by mechanical grinding.

[0049] 2) adding 6 g of ethyl acrylate, 0.08 g of gelatin, 0.04 g of ethylene glycol diacrylamide, and 3.8 g of silver nitrate by weight to 60 mL of an aqueous dispersion containing 5 wt % of sulfonated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0050] 3) At room temperature, 5.4 g of potassium persulfate and 0.2 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 500 s. Embodiment 4

[0051] 1) At room temperature, 0.6 g of bamboo powder was added to 800 mL of water, followed by mechanical stirring until the solution was uniform, and finally mechanical grinding was used to obtain hydroxylated lignin cellulose nanofibrils.

[0052] 2) adding 6.5 g of hydroxyethyl methacrylate, 0.78 g of gelatin, 0.39 g of N,N'-methylenebisacrylamide, and 3.8 g of silver nitrate by weight to 60 mL of an aqueous dispersion containing 15 wt% of hydroxylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0053] 3) At room temperature, 7.4 g of ammonium persulfate and 0.2 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 600 s. Embodiment 5

[0054] 1) At room temperature, 40 g of urea, 6 g of diammonium hydrogen phosphate, and 0.7 g of bamboo powder were added to 600 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 70 ° C for 120 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally phosphorylated lignocellulose nanofibrils were finally obtained by mechanical grinding.

[0055] 2) adding 20.8 g of isobornyl acrylate, 13.06 g of gelatin, 1.14 g of N,N'-bis(acryloyl)cystamine, and 1.04 g of silver perchlorate by weight to 50 mL of an aqueous dispersion containing 15 wt% of phosphorylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0056] 3) At room temperature, 7.98 g of ammonium persulfate and 3.9 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 650 seconds. Embodiment 6

[0057] 1) At room temperature, 20 g of urea, 8 g of ammonium bisulfate, and 0.3 g of bamboo powder were added to 800 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 100 ° C for 60 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally the sulfonated lignin cellulose nanofibrils were finally obtained by mechanical grinding.

[0058] 2) by weight, 40 g of methyl acrylate, 0.78 g of gelatin, 0.08 g of N,N'-methylenebisacrylamide, and 3 g of silver perchlorate were added to 80 mL of an aqueous dispersion containing 5 wt% of sulfonated lignocellulose nanofibrils at room temperature and mixed to form a uniform solution;

[0059] 3) At room temperature, add 4 g of ammonium persulfate and 8 g of dimethyl sulfoxide to the solution obtained in step 2) at room temperature, stir evenly, and then place it at room temperature for 400 seconds. Embodiment 7

[0060] 1) At room temperature, 0.3 g of bamboo powder was added to 700 mL of water, followed by mechanical stirring until the solution was uniform, and finally mechanical grinding was used to obtain hydroxylated lignin cellulose nanofibrils.

[0061] 2) adding 43 g of methacrylic acid, 2.6 g of gelatin, 3.64 g of N,N'-(1,2-dihydroxyethylene)diacrylamide, and 2.07 g of silver perchlorate by weight to 50 mL of an aqueous dispersion containing 50 wt% of hydroxylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0062] 3) At room temperature, 2.28 g of ammonium persulfate and 0.8 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 1200 s. Embodiment 8

[0063] 1) At room temperature, 28 g of urea, 6.4 g of ammonium bisulfate, and 0.42 g of bamboo powder were added to 500 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 100 ° C for 120 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally the sulfonated lignin cellulose nanofibrils were finally obtained by mechanical grinding.

[0064] 2) adding 13 g of hydroxyethyl methacrylate, 26.1 g of gelatin, 2 g of N,N'-(1,2-dihydroxyethylene)diacrylamide, and 0.8 g of silver nitrate to 40 mL of an aqueous dispersion containing 35 wt% of sulfonated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0065] 3) At room temperature, 8.33 g of sodium persulfate and 3.9 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 800 s. Embodiment 9

[0066] 1) At room temperature, 28 g of urea, 4.2 g of diammonium hydrogen phosphate, and 0.5 g of bamboo powder were added to 600 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 80 ° C for 60 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally phosphorylated lignocellulose nanofibrils were finally obtained by mechanical grinding.

[0067] 2) by weight, 72 g of hydroxypropyl methacrylate, 13 g of gelatin, 0.96 g of ethylene glycol diacrylamide, and 0.17 g of silver nitrate were added to 100 mL of an aqueous dispersion containing 5 wt % of phosphorylated lignocellulose nanofibrils at room temperature, and mixed to form a uniform solution;

[0068] 3) At room temperature, 0.27 g of potassium persulfate and 0.08 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 900 s. Embodiment 10

[0069] 1) At room temperature, 39 g of urea, 4 g of diammonium hydrogen phosphate, and 0.7 g of bamboo powder were added to 800 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 80 ° C for 120 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally phosphorylated lignocellulose nanofibrils were finally obtained by mechanical grinding.

[0070] 2) adding 22 g of acrylic acid, 7.83 g of gelatin, 0.7 g of N,N'-methylenebisacrylamide, and 0.03 g of silver nitrate by weight to 40 mL of an aqueous dispersion containing 35 wt% of phosphorylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0071] 3) At room temperature, 6 g of sodium persulfate and 1.56 g of dimethyl sulfoxide were added to the solution obtained in step 2) at room temperature, stirred evenly, and then allowed to stand at room temperature for 400 seconds.

[0072] See attached Figure 1 This is a digital photo of the rapid gelation process of the composite hydrogel synthesized by the present invention. Figure 1 It can be seen that the hydrogel system can gel after standing for a period of time at room temperature. In order to quantify the gel time, the maximum value of the reaction temperature during the gel process is set as the gel time. The temperature of the gel process is monitored by infrared thermal imaging. It can be seen from the figure that after 159s, the temperature of the system reaches the maximum value. Therefore, the gel time of this system is 159s, which is lower than the traditional thermal initiation system (several hours or even dozens of hours).

[0073] See attached Figure 3 This is a digital photo of the mechanical deformation of the composite hydrogel synthesized in Example 10. The hydrogel was subjected to macroscopic mechanical behavior tests such as lifting weights, axial stretching (500%), and plane stretching, and no mechanical failure occurred. This indicates that the hydrogel has excellent mechanical strength and toughness, and further confirms the balanced mechanical properties.

[0074] See attached Figure 4 This is the swelling curve of the composite hydrogel synthesized in Example 10. A cylindrical sample of a certain mass is placed in an excess of deionized water, and samples are taken and weighed at a set time point and calculated. As can be seen from the figure, the composite hydrogel can maintain a low swelling rate (1.032 g / g) in a water environment, indicating that the composite hydrogel can maintain structural stability for a long time in a water environment, making it potential for underwater application.

[0075] See attached Figure 5 The digital photos of the underwater adhesion of the composite hydrogel synthesized in Example 10 to different substrates. The hydrogel sheet was directly in contact with the substrate in a water environment for a period of time, and then photographed and tested for standardized peel strength. As can be seen from the figure, the composite hydrogel has high adhesion to the surfaces of various substrates underwater, and the adhesion strengths with rubber, metal and pig skin can reach 7 kPa, 4 kPa and 6 kPa respectively.

[0076] See attached Figure 6 The digital photos of the composite hydrogels synthesized in Comparative Example 3 and Example 10 under low temperature conditions. The samples of the comparative example and the example were placed under low temperature conditions (-20°C) for a long time (30 days), and then their macroscopic mechanical behaviors were qualitatively tested. As can be seen from the figure, Example 10 has no freezing phenomenon and can maintain high mechanical elasticity and flexibility (stretching, full, torsion, etc.). In contrast, Comparative Example 3 has obvious freezing and completely lost its original high elasticity.

[0077] See attached Figure 7 This is a schematic diagram of the composite hydrogel synthesized in Example 10 being used for underwater Morse code compilation. The hydrogel is used as a sensor, combined with a digital source meter and a wire to form a strain sensing monitoring platform. The Morse code representing "SOS" can be successfully compiled by using electrical pulses represented as dots and lines to send information.

[0078] To further illustrate the excellent performance of the anti-swelling and underwater adhesive conductive composite hydrogel prepared by the present invention, the inventors also conducted the following comparative experiments:

[0079] Comparative Example 1

[0080] 1) By weight, 22 g of acrylic acid and 0.7 g of N,N'-methylenebisacrylamide were added to 40 mL of aqueous solution at room temperature and mixed to form a uniform solution;

[0081] 2) At room temperature, 6 g of sodium persulfate and 0.03 g of silver nitrate were added to the solution obtained in step 1) at room temperature, stirred evenly, and then reacted in an oven at 45° C. for 22 hours to finally prepare a composite hydrogel of comparative example 1.

[0082] Comparative Example 2

[0083] 1) By weight, 22 g of acrylic acid, 7.83 g of gelatin, and 0.7 g of N,N'-methylenebisacrylamide were added to 40 mL of aqueous solution at room temperature and mixed to form a uniform solution;

[0084] 2) At room temperature, 6 g of sodium persulfate and 0.03 g of silver nitrate were added to the solution obtained in step 1) at room temperature, stirred evenly, and then reacted in an oven at 45° C. for 22 hours to finally prepare the comparative example 2 composite hydrogel.

[0085] Comparative Example 3

[0086] 1) At room temperature, 39 g of urea, 4 g of diammonium hydrogen phosphate, and 0.7 g of bamboo powder were added to 800 mL of water, and then mechanically stirred until the solution was uniform. The resulting suspension was poured into a container and dried in a forced air oven to constant weight. The solid obtained above was then placed at 80 ° C for 120 min, dispersed with water and neutralized with alkali solution. The resulting suspension was dialyzed to neutrality, and finally phosphorylated lignocellulose nanofibrils were finally obtained by mechanical grinding.

[0087] 2) adding 22 g of acrylic acid, 7.83 g of gelatin, 0.7 g of N,N'-methylenebisacrylamide, and 0.03 g of silver nitrate by weight to 40 mL of an aqueous dispersion containing 35 wt% of phosphorylated lignocellulose nanofibrils at room temperature, and mixing to form a uniform solution;

[0088] 3) At room temperature, 6 g of sodium persulfate was added to the solution obtained in step 2) at room temperature, and the mixture was stirred evenly. The mixture was then placed at room temperature for 700 seconds to finally prepare the comparative example III composite hydrogel.

[0089] Attached Figure 2 The stress-strain curves of the hydrogels synthesized in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 10. A hydrogel sheet with a length, width and thickness of 2cm*1cm*0.5cm was placed on a film fixture, with an initial distance of 1cm and a stretching speed of 100mm∙min -1. The research and analysis found that due to the introduction of gelatin, lignin cellulose nanofibrils and dimethyl sulfoxide, the composite hydrogel synthesized in Example 10 formed strong physical interactions between polymer chains, and the mechanical properties of the network structure were greatly improved. Therefore, compared with the single-component reinforcement system (Comparative Example 1, Comparative Example 2 and Comparative Example 3), the mechanical parameters of Example 10 are the best: tensile strength: 0.20 MPa, elongation at break: 699%, toughness: 0.9 MJ·m -3 .

[0090] In summary, the hydrogel material prepared by the present invention has fast and controllable room temperature gelation, and also has excellent comprehensive properties, including excellent and balanced mechanical properties, high conductivity, excellent antifreeze properties, excellent underwater adhesion and underwater strain-induced resistance change characteristics.

[0091] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a swelling-resistant, underwater-adhesive conductive composite hydrogel, characterized in that: The method comprises at least the following steps: To 0.1-0.5 parts of an aqueous dispersion containing 5-50 wt% of lignocellulose nanofibrils, 1-5 parts of an acrylic monomer, 0.1-0.5 parts of gelatin, 0.01-0.05 parts of a crosslinking agent, 0.01-0.05 parts of a silver salt and 0.01-0.035 parts of an initiator are added, followed by uniform mixing with 1-5 parts of dimethyl sulfoxide to obtain a gel precursor, which is allowed to stand at room temperature for 200-1200 seconds to obtain the anti-swelling, underwater adhesive conductive composite hydrogel; The lignocellulose nanofibrils are at least one of hydroxylated lignocellulose nanofibrils, phosphorylated lignocellulose nanofibrils, and sulfonated lignocellulose nanofibrils, and the surfaces of the lignocellulose nanofibrils have a catechol structure.

2. The method for preparing the anti-swelling, underwater adhesive conductive composite hydrogel according to claim 1, characterized in that: The preparation method of the lignocellulose nanofibrils is as follows: At room temperature, 4-400 parts of urea, 1-20 parts of an acidifying agent, and 0.5-10 parts of bamboo powder are added to 20-1000 parts of water, followed by mechanical stirring until the solution is uniform, the resulting suspension is poured into a container and dried to constant weight in a blast oven; the resulting solid is then placed at 50-200°C for 30-120 min, dispersed with water and neutralized with an alkali solution; the resulting suspension is dialyzed to neutrality, and lignocellulose nanofibrils are obtained by mechanical grinding; the acidifying agent is diammonium hydrogen phosphate or ammonium hydrogen sulfate.

3. The method for preparing the anti-swelling, underwater adhesive conductive composite hydrogel according to claim 1, characterized in that: The acrylic monomer includes acrylic acid, methyl acrylate, ethyl acrylate, lauryl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, hydroxypropyl methacrylate or methacrylic acid.

4. The method for preparing the anti-swelling, underwater adhesive conductive composite hydrogel according to claim 1, characterized in that: The molecular weight of the gelatin is 5500-250000.

5. The method for preparing the anti-swelling, underwater-adhesive conductive composite hydrogel according to claim 1, characterized in that: The crosslinking agent includes N,N'-methylenebisacrylamide, N,N'-bis(acryloyl)cystamine, ethylene glycol diacrylamide or N,N'-(1,2-dihydroxyethylene)diacrylamide.

6. The method for preparing the anti-swelling, underwater-adhesive conductive composite hydrogel according to claim 1, characterized in that: The silver salt is at least one of silver nitrate and silver perchlorate.

7. The method for preparing the anti-swelling, underwater-adhesive conductive composite hydrogel according to claim 1, characterized in that: The initiator includes ammonium persulfate, sodium persulfate or potassium persulfate.

8. An anti-swelling, underwater adhesive conductive composite hydrogel prepared by the method of claim 1.

9. Application of the anti-swelling, underwater-adhesive conductive composite hydrogel prepared by the method of claim 1 in human motion monitoring and underwater communication sensing.

Citation Information

Patent Citations

  • Anti-swelling and stretchable conductive polymer hydrogel as well as preparation method and application thereof

    CN118184872A

  • Transparent conductive hydrogel with single-sided self-adhesion and preparation method and application thereof

    CN112831062A

  • Gelatin-based conductive hydrogel with high strength and high additional value as well as preparation method and application of gelatin-based conductive hydrogel

    CN114437370A